Perlindungan Hukum Atas Penyelesaian Hukum Tidak Berfungsinya Proses Transaksi Melalui SMART Contract Pada Sistem Blockchain - Mansula, Gabriella (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The purpose of this study is to analyze the characteristics of smart contract user agreements in Indonesia and examine the legal certainty of using smart contracts in relation to contract law in BW. This type of research is doctrinal legal research. With a legal approach as well as a conceptual approach. supporting legal sources, namely primary legal materials and secondary legal materials. The collected material is analyzed using descriptive-qualitative method, ie. also summarizing for the description explains it qualitatively. The results of the study show that the characteristics of smart contracts implemented with blockchain technology and the legal certainty of their application are not in accordance with the principles of freedom of contract and the subjective part of commitments. The increasingly widespread use of the internet is now affecting the global economy which is marked by the emergence of electronic commerce. E-commerce mechanisms that do not directly bring together sellers and buyers raise various questions related to the subjective and objective conditions of the sale and purchase contract. Therefore, the purpose of this article is to analyze the urgency of using the smart contract technology-based contract concept in online buying and selling transactions. Based on the results obtained, the use of smart contracts in electronic business buying and selling transactions is considered very important given its advantages in terms of security, authentication, modification of contract contents and value. Keywords: Law; Blockchain; Smart Contract.